1996
DOI: 10.1074/jbc.271.30.18095
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of the Fc Receptor γ-Chain in Collagen-stimulated Platelets

Abstract: Stimulation of platelets by the extracellular matrix protein collagen leads to activation of a tyrosine kinasedependent mechanism resulting in secretion and aggregation. Tyrosine phosphorylation of the tyrosine kinase Syk and phospholipase C ␥ 2 are early events in collageninduced activation. We recently proposed that collagensignaling in platelets involves a receptor or a receptorassociated protein containing an immunoreceptor tyrosine-based activation motif (ITAM) enabling interaction with Syk. In this repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
204
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(216 citation statements)
references
References 39 publications
10
204
0
2
Order By: Relevance
“…Syk is upstream in mediating high affinity IgE receptor (Fc⑀RI) (17), Fc receptor ␥-chain RII (19,47), IL-2R (48), and CD40 (49). Recently, Toll-like receptor (TLR)-2 or TLR-4 has been proven to mediate LPS-induced cellular signaling (50 -52).…”
Section: Discussionmentioning
confidence: 99%
“…Syk is upstream in mediating high affinity IgE receptor (Fc⑀RI) (17), Fc receptor ␥-chain RII (19,47), IL-2R (48), and CD40 (49). Recently, Toll-like receptor (TLR)-2 or TLR-4 has been proven to mediate LPS-induced cellular signaling (50 -52).…”
Section: Discussionmentioning
confidence: 99%
“…The pellets were washed in lysis buffer followed by Trisbuffered saline (TBS-T; 20 mM Tris, 137 mM NaCl, 0.1% (v/v) Tween 20, pH 7.6) before the addition of Laemmli sample treatment buffer in preparation for SDS-PAGE. A GST fusion protein containing the tandem SH2 domains of Syk was prepared and used to precipitate the FcR ␥-chain as described previously (12).…”
Section: Methodsmentioning
confidence: 99%
“…The Src-like kinases Fyn and Lyn are believed to be involved in this phosphorylation (9 -11). Syk is able to bind to the tyrosine-phosphorylated ITAM of the FcR ␥-chain via its tandem SH2 domains (12) leading to autophosphorylation and activation. Syk plays a critical role in the regulation of PLC␥2 through phosphorylation of a number of key proteins including the adapters LAT and SLP-76 (13)(14)(15).…”
mentioning
confidence: 99%
“…PKC may also play a role in the stabilizing function of other platelet collagen receptors. [37][38][39][40] Although there have been no studies of PKC involvement in platelet adhesion under flow conditions, several reports indicate that PKC inhibitors block adhesion under static conditions. In particular, Vuori and Ruoslahti 9 reported that calphostin C inhibits fibroblast adhesion to fibronectin.…”
Section: Discussion Platelet Adhesion To Collagen: Activation Of Pkc mentioning
confidence: 99%
“…35 Platelet adhesion under these conditions is very efficient, occurring within seconds, and in a plasma-free, Mg 2ϩ -containing buffer it is mediated primarily by the ␣ 2 ␤ 1 -integrin, 36 although other receptors or associated proteins may participate. [37][38][39][40] In the present study, we investigated the involvement of PKC in platelet adhesion to collagen under flow conditions by using several PKC inhibitors. In cases of vessel-wall injury, not only must platelet adhesion to the exposed adhesive proteins of the ECM be rapid (seconds to minutes), but also, the stability of the attached platelets must be sufficient to prevent blood loss and contribute to the healing process.…”
mentioning
confidence: 99%